Applying fuzzy dematel method based on simplified centroid defuzzification for solving the supplier selection problem in fertigation system / Asyura Abd Nassir …[et al.] - Abd Nassir, Asyura; Mohd, Ainun Hafizah; Mohd Bahkri, Nur Hazirah; Ramli, Nazirah (Universiti Teknologi MARA Cawangan Pahang, 2021)
Fertigation is an innovative agricultural technique that can maximise crop yields. Since the fertigation system is widely used, deciding the best supplier selection becomes crucial. Fuzzy Decision-Making Trial and Evaluation Laboratory (DEMATEL) method is a useful method for solving the Multicriteria Decision-Making (MCDM) in supplier selection problems. This study aims to identify the importance weights of criteria and the influence relationships among criteria in the fertigation system using the fuzzy DEMATEL method based on simplified centroid defuzzification. The fuzzy DEMATEL method consists of 6 steps whereby the simplified centroid defuzzification based on the pointwise operation was implemented in the procedure. This study also used secondary data from previous research, focusing on six supplier selection criteria relevant to the fertigation system: price, quality, delivery, public procurement policy, technical aspect, and managerial aspect. The results found that the technical aspect is the most influential criterion for supplier selection in the fertigation system. Further, this result can serve as a useful guide in determining the best selection of suppliers in the fertigation system using fuzzy DEMATEL based on the other defuzzification method.